Optimization of alginate and gellan-based edible coating formulations for fresh-cut pineapples - Azarakhsh, Nima; Osman, Azizah; Tan, Chin Ping; Mohd Ghazali, Hasanah; Mohd Adzahan, Noranizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The effects of alginate-based [sodium alginate, 0-2% (w/v), glycerol, 0-2% (w/v) and sunflower oil 0.025% (w/v)] and gellan-based [gellan, 0-1% (w/v), glycerol, 0-1% (w/v) and sunflower oil 0.025% (w/v)] edible coatings on fresh-cut pineapple were evaluated by response surface methodology (RSM). Weight loss, firmness and respiration rate were considered as response variables. The results showed that for all response variables the RSM models were significantly (p<0.05) fitted. Regression models indicated R 2 (high coefficient of determination) values ranging from 0.931 to 0.955 and 0.949 to 0.968 for alginate and gellan-based coatings, respectively. There was no significant (p>0.05) difference between predicted and experimental values. The overall optimum region predicted by RSM indicated that alginate and gellan-based coatings containing 1.29% (w/v) sodium alginate, 1.16% (w/v) glycerol and 0.56% (w/v) gellan gum, 0.89% (w/v) glycerol were optimized formulations respectively.